(3GdeNJUQ GdfGaYs - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj UZQJ aj YXeJg YHGOI GdYGHOjf (B... (3aEfj ehQO dc aj gPG GdeNJUQ NdGUI GdePgH GdeYJHQ HCdaGX eMHQI hYHGQIs
(3BNQgG (B:s
(3BNQgG(B: (3hdh cGf aj CMOjgeG aKdK OjJgeG heY GdHQA NeS OjJgeG EPG GfaPJ fGaPI aj TjA ef CWQGa GdQLd aOjJgeG eGFI OjfGQ, GdQGHYI aj GMeQGQ GdhLg HGdLfGjI OjfGQ hfUas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 123s
(3GdPQjYI, L (B20: 141s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis